Penguatan Wawasan Kebangsaan kepada Pengurus Karang Taruna di Kabupaten Lombok Tengah - Khaerul Anam; Yadi Imansyah; Lilik Evitamala; Hasbi Hasbi; Muhammad Riyan Hidayatullah (Nusantara Mengabdi Kepada Negeri, 2024)
The management of Karang Taruna plays a strategic role in maintaining and strengthening unity and national awareness within the community. However, there remains a gap in understanding related to national awareness, particularly among the youth involved in Karang Taruna in Central Lombok Regency. This issue serves as a significant backdrop for community service aimed at enhancing the understanding and appreciation of national awareness. This program aims to provide reinforcement of national awareness to Karang Taruna administrators across Central Lombok Regency through an integrated training and mentoring program. The method used in this activity is a participatory approach, involving stages of socialization, training, focus group discussions, and continuous evaluation. The training includes expert speakers in the fields of nationalism and leadership, combined with case studies and real-life simulations. The results of this community service show a pre-test score of 55% and a significant increase to 88% in the post-test on participants' understanding of national awareness, as measured through pre and post-test evaluations. Additionally, there was a 90% increase in motivation and sense of responsibility among participants in fostering national spirit within their respective communities. In-depth discussions with participants indicate that practical and interactive approaches in training are more effective in enhancing understanding of abstract concepts of nationalism compared to conventional lecture methods. It is hoped that through this reinforcement of national awareness, Karang Taruna administrators can become change agents who promote unity, harmony, and national spirit in their regions